2017
DOI: 10.1007/s00253-017-8185-9
|View full text |Cite
|
Sign up to set email alerts
|

Fungi-based treatment of brewery wastewater—biomass production and nutrient reduction

Abstract: The beer-brewing process produces high amounts of nutrient-rich wastewater, and the increasing number of microbreweries worldwide has created a need for innovative solutions to deal with this waste. In the present study, fungal biomass production and the removal of organic carbon, phosphorus and nitrogen from synthetic brewery wastewater were studied. Different filamentous fungi with a record of safe use were screened for growth, and Trametes versicolor, Pleurotus ostreatus and Trichoderma harzianum were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…Moreover, a previous study showed that the SS and BOD 5 removal efficiencies were 87 and 93% respectively in a domestic WWTP in Turkey ( Tanyol and Demir, 2016 ). In wastewater treatment ecosystems, fungal strains can remove phosphorus and nitrogen from wastewater ( Hultberg and Bodin, 2017 ). Together, these results revealed that there were significant improvements in wastewater qualities after biochemical treatment process.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a previous study showed that the SS and BOD 5 removal efficiencies were 87 and 93% respectively in a domestic WWTP in Turkey ( Tanyol and Demir, 2016 ). In wastewater treatment ecosystems, fungal strains can remove phosphorus and nitrogen from wastewater ( Hultberg and Bodin, 2017 ). Together, these results revealed that there were significant improvements in wastewater qualities after biochemical treatment process.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, researchers who have previously conducted research on the P removal from municipal wastewater under batch experiments, have also presented a fungal ability to reduce P where the removal efficiency has varied from 12 to 100 % (Hultberg and Bodin, 2017;Sankaran et al, 2010;Ye et al, 2015). For example, Hultberg and Bodin (2017) investigated the pH effect on the P removal by using fungi in synthetic brewery wastewater (Hultberg and Bodin, 2017). In addition, results showed there was no significant effect on the pH level.…”
Section: Phosphorus Removalmentioning
confidence: 99%
“…Furthermore, all of these transformations are developed together to be combined with the enzyme system and the ability of adsorption, deposition and ion exchange (Dalecka et al, 2020a,b;Pedroza-Rodríguez and Rodríguez-Vázquez, 2013). However, most of the studies investigated the removal of pharmaceutical substances from municipal wastewater using laboratory strains from culture collections, including T. versicolor (He et al, 2019;Hultberg and Bodin, 2017;Spina et al, 2012). Therefore, Guest and Smith (2007) have suggested using fungi that are naturally available in a municipal wastewater treatment plant due to their adaptation to the environmental and operation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the subdivisions, beverage industries in Ethiopia cause high pollution problems by discharging their untreated or partially treated effluents into nearby water bodies and irrigated soils (Oljira et al 2018). Since brewery wastewater contains variable pollutants such as carbohydrates, alcohols, suspended solids, yeast (Mohan et al 2018); proteins, ethanol, and volatile fatty acids (Raposo et al 2010); nutrients, refractory organics, and pathogens (Hultberg and Bodin 2017).…”
Section: Introductionmentioning
confidence: 99%